KEKERASAN SEKSUAL PADA ANAK MENURUT HUKUM OSITIF DAN HUKUM ISLAM - Madiha Dzakiyyah Chairunnisa; Ii Rijalulloh (Istinbath | Jurnal Penelitian Hukum Islam, 2018)
Child rights are protected in Article 28 (B) (2) of the 1945 Constitution which reads that every child has the right to survival, growth and development and is entitled to protection from violence and discrimination. In recent years there has been a rampant case of sexual abuse of minors and the perpetrator being a more mature person, and allegedly known by his own victims. Factors causing this sexual harassment occur because of the many influences from foreign cultures that enter the country. Like elements in movies and so forth. In addition, the weakness of the legislation system to ensnare the perpetrators, as well as the weak quality of the perpetrator's religion. How does a positive legal review of child sexual abuse (pedophilia), as well as an overview of Islamic law on child sexual abuse (pedophilia)